2018
DOI: 10.3389/fmars.2018.00014
|View full text |Cite
|
Sign up to set email alerts
|

High Latitude Corals Tolerate Severe Cold Spell

Abstract: Climatically extreme weather events often drive long-term ecological responses of ecosystems. By disrupting the important symbiosis with zooxanthellae, Marine Cold Spells (MCS) can cause bleaching and mortality in tropical and subtropical scleractinian corals. Here we report on the effects of a severe MCS on high latitude corals, where we expected to find bleaching and mortality. The MCS took place off the coast of Perth (32 • S), Western Australia in 2016. Bleaching was assessed before (2014) and after (2017)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The third option for maintaining more desirable ecosystem states than turf is to accelerate adaptation/movement of corals into cooler waters. Naturally recruited corals inhabiting high latitude reefs areas appear tolerant to cooler waters including cold spells (Tuckett & Wernberg, ), but can still be susceptible to bleaching during warm thermal events (Hughes et al, ). Assisting the migration of more thermally tolerant corals may be beneficial to coral persistence at higher latitudes, however, there are still major knowledge gaps including the heritability of traits in corals and/or symbionts (van Oppen et al, ).…”
Section: Approaches To Managing Tropicalised Reefsmentioning
confidence: 99%
“…The third option for maintaining more desirable ecosystem states than turf is to accelerate adaptation/movement of corals into cooler waters. Naturally recruited corals inhabiting high latitude reefs areas appear tolerant to cooler waters including cold spells (Tuckett & Wernberg, ), but can still be susceptible to bleaching during warm thermal events (Hughes et al, ). Assisting the migration of more thermally tolerant corals may be beneficial to coral persistence at higher latitudes, however, there are still major knowledge gaps including the heritability of traits in corals and/or symbionts (van Oppen et al, ).…”
Section: Approaches To Managing Tropicalised Reefsmentioning
confidence: 99%
“…However, the response of these corals to cold stress events has not been tested. The reefs of the GoA are some of the northernmost in the world; limited research has suggested that high latitude corals may have greater tolerance to cold stress than their tropical conspecifics (Tuckett & Wernberg, 2018). In the northernmost part of the GoA, a steep slope from the forereef to a depth of 40-100 m may prevent major cold-water events on the shallow reef since denser cooler water will sink to greater depth.…”
Section: Introductionmentioning
confidence: 99%
“…Since bleaching severity following cold water stress has previously been shown to be species specific (Coles & Fadlallah, 1991;Zapata, Jaramillo-González & Navas-Camacho, 2011;Kemp et al, 2016;Pontasch et al, 2017;Tuckett & Wernberg, 2018), the responses of two species were compared in this study. Acroporid corals are the most abundant scleractinian genera in Eilat with Stylophora sp.…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed tested. The reefs of the GoA are some of the northernmost in the world; limited research has suggested that high latitude corals may have greater tolerance to cold stress than their tropical conspecifics (Tuckett & Wernberg, 2018). In the northernmost part of the GoA, a steep slope from the forereef to a depth of 40-100 m may prevent major cold-water events on the shallow reef since denser cooler water will sink to greater depth.…”
Section: Introductionmentioning
confidence: 99%
“…Since bleaching severity following cold water stress has previously been shown to be species specific (Coles & Fadlallah, 1991;Zapata, Jaramillo-González & Navas-Camacho, 2011;Kemp et al, 2016;Pontasch et al, 2017;Tuckett & Wernberg, 2018), the responses of two species were compared in this study. Acroporid corals are the most abundant scleractinian genera in Eilat with Stylophora sp.…”
Section: Introductionmentioning
confidence: 99%